2007
DOI: 10.1080/10715760701416442
|View full text |Cite
|
Sign up to set email alerts
|

Lipid oxidation predominates over protein hydroperoxide formation in human monocyte-derived macrophages exposed to aqueous peroxyl radicals

Abstract: In U937 and mouse myeloma cells, protein hydroperoxides are the predominant hydroperoxide formed during exposure to AAPH or gamma irradiation. In lipid-rich human monocyte-derived macrophages (HMDMs), we have found the opposite situation. Hydroperoxide measurements by the FOX assay showed the majority of hydroperoxides formed during AAPH incubation were lipid hydroperoxides. Lipid hydroperoxide formation began after a four hour lag period and was closely correlated with loss of cell viability. The macrophage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Oxidative stress is a fundamental underpinning of a number of neurodegenerative diseases, including HAD, the most severe form of HAND. Several studies point to HIV‐1 Tat's mediation of oxidative stress in astrocytes as possibly leading to cell death (Firth et al,2007). One mechanism through which oxidative stress is able to impact signaling pathways and their downstream transcription factors is via a respiratory burst orchestrated by the activation of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a fundamental underpinning of a number of neurodegenerative diseases, including HAD, the most severe form of HAND. Several studies point to HIV‐1 Tat's mediation of oxidative stress in astrocytes as possibly leading to cell death (Firth et al,2007). One mechanism through which oxidative stress is able to impact signaling pathways and their downstream transcription factors is via a respiratory burst orchestrated by the activation of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Human peripheral blood monocytes were isolated from the blood of healthy volunteers using Lymphoprep, as described previously [38]. This project has been reviewed by the University of Reading Research Ethics Committee and has been given a favourable opinion for conduct.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, in HIVE oxidative stress markers have been found to co-localize with glial cells and neurons (Pocernich et al 2005b). Several studies point to the effect of HIV-1 Tat in mediating oxidative stress in astrocytes (Blokhina et al 2003; Nath 2002; Pocernich et al 2005a; Pocernich et al 2005b; Saha and Pahan 2007; Viviani et al 2001) possibly leading to cell death (Firth et al 2007; Muscoli et al 2002; Viviani et al 2001). Furthermore, it has also been demonstrated that HIV-1 induced oxidative stress in astrocytes can regulate target genes that are under the control of NF-κB, one of the essential transcription factors responsible for CXCL10 induction (Song et al 2007).…”
Section: Introductionmentioning
confidence: 99%